2012
DOI: 10.1021/ja2108855
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Directed Acyl Imidazole Chemistry for Labeling of Membrane-Bound Proteins on Live Cells

Abstract: Chemistry-based protein labeling in living cells is undoubtedly useful for understanding natural protein functions and for biological/pharmaceutical applications. Here, we report a novel approach for endogenous membrane-bound protein labeling for both in vitro and live cell conditions. A moderately reactive alkyloxyacyl imidazole (AI) assisted by ligand-binding affinity (ligand-directed AI (LDAI)) chemistry allowed us to selectively modify natural proteins, such as dihydrofolate reductase (DHFR) and folate rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
162
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(171 citation statements)
references
References 31 publications
2
162
0
Order By: Relevance
“…Parallel labeling experiments against the target protein carbonic anhydrase have shown that the moderately reactive epoxide crosslinker exhibits the optimal balance of selectivity and reactivity (Chen et al 2003). Hamachi, Fenical and their respective co-workers developed a series of novel traceless affinity labeling probes containing electrophilic organocatalysts such as acyl phenolate, (Hughes et al 2009) 4-dimethylaminopyridine (DMAP) (Koshi et al 2008;Sun et al 2011;Wang et al 2011), tosylate, (Tsukiji et al 2009a, b;Tamura et al 2012), and acyl imidazole (Fujishima et al 2012;Matsuo et al 2013;Miki et al 2014). By targeting specific nucleophilic groups in the ligand-binding pocket of the protein, these probes exhibited high target specificity (Fig.…”
Section: Covalent Crosslinkingmentioning
confidence: 99%
“…Parallel labeling experiments against the target protein carbonic anhydrase have shown that the moderately reactive epoxide crosslinker exhibits the optimal balance of selectivity and reactivity (Chen et al 2003). Hamachi, Fenical and their respective co-workers developed a series of novel traceless affinity labeling probes containing electrophilic organocatalysts such as acyl phenolate, (Hughes et al 2009) 4-dimethylaminopyridine (DMAP) (Koshi et al 2008;Sun et al 2011;Wang et al 2011), tosylate, (Tsukiji et al 2009a, b;Tamura et al 2012), and acyl imidazole (Fujishima et al 2012;Matsuo et al 2013;Miki et al 2014). By targeting specific nucleophilic groups in the ligand-binding pocket of the protein, these probes exhibited high target specificity (Fig.…”
Section: Covalent Crosslinkingmentioning
confidence: 99%
“…These specific recognition-derived results suggested high expression of FA receptors on MCF-7 cells, moderate expression on HepG2 cells, and no expression on normal cells, which was in accord with flow cytometric analysis using fluorescence-labeling , confirming the validity of the proposed method. The signal for receptor expression was directly observed during RRS detection, which was more quantitative and facile than microscopic observation (Fujishima et al, 2012).…”
Section: Utility Of Cytosensor For Sensing Fa Receptors Expressionmentioning
confidence: 99%
“…Current efforts for cells recognition and cell surface antibody analysis have been focused on the usage of biochips (Culha et al, 2004;Kwong et al, 2009;Ellis et al, 2012), flow cytometry , fluorescence-labeling imaging (Fujishima et al, 2012), and the theoretical calculation (Li et al, 2015). Although these methods are powerful for molecular details, they have shortcomings of cellular auto-fluorescence, time-consuming sample preparation, and sophisticated instrumentation.…”
Section: Introductionmentioning
confidence: 99%
“…From a standpoint of organic chemistry, it is also crucial to expand the repertoire of organic reactions that can be used for traceless affinity labeling of proteins in biological conditions. For instance, we have recently developed two new techniques, the affinity-guided 4-dimethylaminopyridine (DMAP) (AGD) chemistry [43][44][45] and the ligand-directed acyl imidazole (LDAI) chemistry [46,47], both of which allow rapid selective native protein labeling. Other promising ligand-directed chemistries have also recently been emerging [48][49][50][51][52].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%